Organizational culture and its impact on continuous improvement in manufacturing - Muthukumar, N.; Ganesh, K.; Mohapatra, Sanjay; Tamizhjyothi, K.; Nachiappan, R. M.; Bharati, M. (Emerald Publishing Limited, 2022)
As manufacturing companies become global, excellence will be key to the survival of Indian manufacturing businesses. Despite India's good performance on the export front in recent years, India is being outperformed by its competitors. Indian manufacturing companies must compete with global companies and become world class organizations to be competitive. Organizational Culture and its Impact on Continuous Improvement in Manufacturing presents detailed insights into recent studies, providing solutions that can be scaled up at a global level. The lack of competitiveness of Indian companies is attributed to culture in the organization as well as an inability to introduce world class manufacturing tools which would allow them to become globally competitive. All the qualities needed to become world class are not currently available, and it is imperative to understand this gap through the detailed research this book presents to ensure India's manufacturing companies can compete.